LEXICAL FEATURES IN THE TEXT OF PRABOWO SUBIANTO'S PRESIDENTIAL INAUGURATION SPEECH IN 2024 - Mustafa, Zaky Faishal; Budiawan, Raden Yusuf Sidiq; Ulfiyani, Siti (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Political speeches play a strategic role in conveying ideological messages and constructing meaning that influences public opinion. In the Indonesian political context, the presidential inauguration speech is a crucial moment that not only reflects the leadership vision but also serves as a means to construct a national narrative, strengthen leadership legitimacy, and symbolically convey the government's agenda. This study aims to describe the use of lexical features in President Prabowo Subianto's 2024 inauguration speech. This study uses a qualitative descriptive approach with distributional analysis techniques to identify and examine the lexical elements that shape meaning and ideology in the speech text. The focus of the study includes classification patterns, ideological vocabulary, lexicalization, meaning relations, euphemistic expressions, and the use of metaphors. The results of the study indicate that the speech represents a strong ideological construction, marked by the dominance of national narratives, calls for unity, and the affirmation of the people's role as the main axis of power. The choice of diction in the speech reflects a political communication strategy that is not only persuasive, but also ideological, thus playing a significant role in shaping public perception of national leadership figures. These findings confirm that lexical features in political speeches function more than just rhetorical tools for President Prabowo Subianto, but also serve as effective ideological instruments in directing discourse and shaping public opinion. This research demonstrates that the language of inaugural speeches needs to be understood not only from a surface semantic perspective but also from an ideological perspective, as it reflects specific interests and plays a crucial role in hegemonic processes. This research contributes to critical discourse studies in the Indonesian political context, particularly in understanding how power is mediated through language. These findings are expected to serve as a reference for further research on linguistic strategies in political communication.